EFEKTIVITAS PENGELOLAAN SAMPAH OLEH DINAS LINGKUNGAN HIDUP DAN KEBERSIHAN KOTA PEKANBARU - Averil, Gerri; ", Ernawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
The study is done in the environmental and cleanliness ( dlhk ) city pekanbaru.The department of environmental and cleanliness ( dlhk ) city pekanbaru is weak support to the operation of the waste management.Today handling of the waste problem in urban area pekanbaru could not going well.This is because the area of service with greater number of heap of garbage high and supporting facilities and infrastructures hygiene inadequate.Research purposes: ( 1 ) to know the effectiveness of waste management by the environment and the city cleansing pekanbaru; ( 2 ) to know the barrier driving and factors affecting the effectiveness of waste management by the environment and the city cleansing pekanbaru.Informants research was taken from the head of waste management, head of reducing and the use of garbage, handling and processing of the trash, gives the infrastructure, and the city pekanbaru.This research using research qualitative descriptive to technique data collection covering interview, observation and study documentation.Based on the research done , that the effectiveness of waste management by the environment and cleanliness the city of pekanbaru done using indicators ( 1 ) clarity the purpose to accomplished; ( 2 ) clarity strategy the achievement of a goal; ( 3 ) process of analysis and the formulation of policies that steady; ( 4 ) programs established proper; ( 5 ) the availability of facilities and infrastructure .Factors - factors affect the effectiveness of waste management by the environment and cleanliness the city of pekanbaru is: ( 1 ) of human resources ( 2 ) facilities and infrastructure ( 3 ) the role of the people ( 4 ) communication. Several factors supporters city waste management pekanbaru by dlhk is affecting in laksanakannya socialization and education waste management right and either to the community, it is just some indonesians not participate in the event.Officers team that has spread have done deterrent for society not to his litter promiscuously and throw garbage into the tela determined.The government also has spread billboards containing the appeal to not littering and disposing of garbage at that we have set.Keywords: waste management, effectiveness, garbage